Pendokumentasian Tradisi Batagak Pangulu Di Lembaga Kerapatan Adat Nagari Situjuah Gadang Kabupaten Lima Puluh Kota - Nurdini, Nurdini (Universitas Negeri Padang, 2024)
Batagak pangulu is the process of appointing traditional leaders in Minangkabau. The lack of information about this culture will certainly have an impact on future generations. This research aims to find out the batagak pangulu documentation management model carried out at KAN Situjuah Gadang with the final result in the form of a thesis. The research method used is a qualitative research method with a case study approach. Data sources were obtained from interviews with informants and document studies related to Batagak Pangulu. The results of the research show that the recording of this tradition is an effort made in maintaining intangible cultural heritage that can be used as a learning resource for future generations in Situjuah Gadang village.